Implementation of Contextual Approach with Group Investigation Learning Model to Improve Social Skills of Class X-3 Students SMA Negeri 1 Boyolali in the School Year 2012/2013 - Chandra Adi Prabowo; Puguh Karyanto; Baskoro Adi Prayitno; Ristanti Yustin (Universitas Sebelas Maret, 2015)
The purpose of the research is to improving the social skill of the class X-3 students SMA Negeri 1 Boyolali in the school year 2012/2013 by applying the contextual approach with Group Investigation learning model. Research method was a Classroom Action Research with two cycles encompassing four stages: planning, acting, observing, and reflecting. The subject of research was the class X-3 students SMA Negeri 1 Boyolali in the school year of 2012/2013. The data was obtained using non-test technique including interview and questionnaire. The research data was analyzed using a descriptive qualitative technique as well as data validation using technique triangulation. The result of the research showed the improved achievement of student social skills. The conclusion is the social skill of the class X-3 students of SMA Negeri 1 Boyolali in the school year of 2012/2013 could be improved by the application of contextual approach using Group Investigation learning model.Keywords: contextual approach, group investigation, social skills